KOLABORASI ORANG TUA DAN GURU DALAM UPAYA PENCEGAHAN BULLYING VERBAL KELAS IV DI SDN BANJARANYAR 04 - Kholifatul Syajiah; Muamar; Dedi Romli Triputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the forms of collaboration between parents and teachers in preventing verbal bullying in the fourth grade of SDN Banjaranyar 04. The research method used was qualitative with a case study approach. Informants consisted of a homeroom teacher, two parents, and four students. Data were collected through interviews, observation, and documentation, and then analyzed using the Miles and Huberman model. The results showed that teachers applied a sympathetic and persuasive approach in guiding students and used motivational strategies, while the sanctions imposed were educational in nature. Parents played a role through firm yet nurturing parenting and maintained active communication with teachers, especially through digital media. Collaboration between the two parties took place informally and had not yet been structured in a systematic manner. The challenges encountered included limited teacher supervision and the presence of harsh parenting at home, which could trigger aggressive behavior. This study underscores the importance of synergy between parents and teachers in creating a safe and supportive learning environment free from verbal bullying.